Refusing to Smile for the Patriarchy - MacDonald, Shana (International Association for the Fantastic in the Arts, 2019)
This article considers how season one of Netflix’s Jessica Jones functions as a feminist revenge narrative that situates the titular protagonist as a survivor of patriarchal abuses at the hands of her ex-boyfriend and supervillain Kilgrave. The article explores how Jessica embodies Sara Ahmed’s concept of the feminist killjoy. Jessica is a feminist anti-hero who provides an alternative, angry, superhumanly strong avatar of women’s everyday negotiations with misogynist excesses. The article reads her as a flawed character who importantly fails the perfectionism tied to postfeminist and neoliberal requirement of contemporary women. This makes her both sympathetic and resonant in the current moment of feminism. As both a symbolic figure and a site of catharsis, the article considers Jones’s journey to greater forms of agency in her fight against Kilgrave.